Kajian Etnomedisin dalam Pengobatan Tradisional pada Ulkus Kaki Diabetik (UKD) di Bali - Rahayu, Luh Risma Putri; Sanjaya, Dwi Arymbhi; Yuda, Putu Era Sandhi Kusuma; Cahyaningsih, Erna; Dewi, Ni Luh Kade Arman Anita; Putra, Made Agus Deny Mahendra (Jurnal Farmasi Udayana, 2021)
One of the complications that occur due to diabetes mellitus (DM) is Diabetic Foot Ulcer (UKD). UKD is an incidence of injuries that occur on the feet of people with diabetes due to complications of microangiopathy and macroangiopathy which can cause disability and even death. This study aims to identify and document traditional medicine used by traditional healers in Bali to treat UKD. This research was conducted using a comparative qualitative descriptive method that compares the data obtained from in-depth interviews and questionnaires filling with literature. Data collection was carried out by in-depth interviews with BATTRA in Bali as informants who have competence in the field of traditional UKD medicine. Determination of informants in this study using snowball sampling technique. The results of the research were carried out from the data obtained by 8 (eight) sources and obtained 10 ingredients, consisting of 6 (six) ingredients used topically and 4 (four) ingredients used orally. The main ingredient used in topical ingredients is honey. Of the 10 ingredients, there are 15 types of medicinal plants used for the treatment of UKD. Most of the medicinal plants used are aloe vera, garlic, pepper, onion and sandalwood .